The perception of special education teachers towards the involvement of audiologist in special education school - Yasin, Mohd Hanafi Mohd; Tahar, Mohd Mokhtar; Mohamad, Suziyani; Rasilah, Nurul Ezza Aleyza Binti; Azirun, Rabaishah (Journal of ICSAR, 2023)
Audiologists is an individual that has close connection with deaf and hearing impairment students. This research is done to study the perception of the special education teachers on the involvement of audiologists in special education school. In this research, quantitative data which is questionnaire is used as the research instrument. The data obtained were analyzed using Microsoft Excel XLstat. The total of 165 teachers that are included in this research through snow-balling sampling. Results shown that 149 (90.8 percent) of the teachers agreed that the role of audiologists is vital to improve the special education quality in Malaysia. In general, the teachers have high comprehency toward the common function of the audiologists but a very worrying understanding on their specific role. It is proven when special education teachers are unsure about whether audiologists only work in hospitals (56 teachers (33.9 percent)), involved in balance problems (65 teachers (39.4 percent)) and vestibular problems (88 teachers (53.3 percent)). The research shown that having an audiologist helps to reduce the impact of hearing loss for the deaf students when 152 (83.8 percent) special education teachers agreed that the involvement of audiologists in the education system benefits many teachers and students thus prepares a better and more condusive environment for them.